BUILD A BUSINESS TO CUSTOMER ONLINE STORE USING AIRZONE CONTENT MANAGEMENT SYSTEM - Untung Rahardja; Qurotul Aini; Desi Sartika (CCIT Journal, 2015)
Current world trade are no longer constrained by space and time. Human mobility is high demanding world trade is able to provide goods and services quickly in accordance with the request of the consumer. Advances in technology and a growing current of information increasingly make online sites provide such services in various fields, especially in the business world that leads to an online transaction activity.Online transactions is better known under the name of e-Commerce that links between the B2B, B2C, C2B, and P2P. Airzone is one form of a system that uses e-commerce as a medium to conduct business in the world of the internet by using the methodology of B2C. Internet users are growing in Indonesia, making the e-Commerce is increasingly required by the company to continue to develop its business activities. Thus Airzone is present in the world of e-commerce is to be able to update the implementation of e-commerce in favor of a business. E-commerce in the world of technology is important in running the buying and selling of companies and organizations, so that the existence of a system of e-commerce makes it easy for businesses to address the assessed transaction activity is still less effective and efficient. So that it can serve as a means of airzone for product development, promotion, online transactions, product delivery and after sales support that will mutually support each other to gain revenue and profit are better.